2012
DOI: 10.5539/ells.v2n1p47
|View full text |Cite
|
Sign up to set email alerts
|

Stylistic Features of Scientific English: A Study of Scientific Research Articles

Abstract: This study intends to explore what stylistic features characterize scientific English and make it different from any other language used in any other discipline. What are certain areas of language that are used more frequently in science than in non-science oriented language texts? This paper deals with the linguistic features concerning the application of vocabulary, grammar, discourse and style used in scientific English. A comparative analysis of literary and scientific language has been undertaken to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…Heslot (1982) examines the main sections (Introduction, Methods, Results and Discussions) of 16 research articles from the journal Phytopathology. The results show that the methodological part has the highest use of the passive among others, which is further confirmed in Ahmad's (2012) research on medical and natural sciences. Swales (1990) points out that cross-disciplinary variation is a factor which cannot be ignored when studying the features of research articles, and still he does not study such variation from the perspective of the voice.…”
Section: Literature Reviewsupporting
confidence: 77%
See 1 more Smart Citation
“…Heslot (1982) examines the main sections (Introduction, Methods, Results and Discussions) of 16 research articles from the journal Phytopathology. The results show that the methodological part has the highest use of the passive among others, which is further confirmed in Ahmad's (2012) research on medical and natural sciences. Swales (1990) points out that cross-disciplinary variation is a factor which cannot be ignored when studying the features of research articles, and still he does not study such variation from the perspective of the voice.…”
Section: Literature Reviewsupporting
confidence: 77%
“…Walpole (1979), in his defense of the passive voice, proposes that passivization is a crucial tool in modern prose for its clearness and brevity, and such a stylistic feature is embodied, for example, in scientific studies and historical writings. Others (Ahmad, 2012;Ding, 2002;Dorgeloh, 2004;Gilbert, 1976;Hyland, 1994;Kopple, 1994) credit impersonality and detachment to the use of passives, though this rhetorical device is condemned as "a form of naïve hypocrisy at best or intellectual dishonesty at worst" by Pruitt (1968). Some grammar books (Celce-Murcia & Larsen-Freeman, 1999;Sinclair, 1990) bear a more objective view in regard to its use, believing that passives are more frequently used in the academic field.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The frequent occurrence of active voice construction has similarity with Ahmad (2012) method and result have higher passive voice construction. However, the difference is that in this corpus based study the total of active voice construction (64.8%) is higher than that of passive voice construction, while the active voice in Ahmad"s study covers only 30%, less than the passive voice construction.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 86%
“…Passive voice construction is mainly used in method section to get rid of personal whims and fancies, and thus obtain impersonality and universality of the research (Ahmad, 2012). Ahmad found that 70% of passive was implemented in method of Medical and Natural Science articles; however, the use of active voice construction was higher in other sections.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific writing differs from other genres of writing in that scientific language is characterized as formal, informative, consistent, straightforward, concise, comprehensible and brief (Ahmad, 2012). A scientist message would be misunderstood if he / she uses complicated or ambiguous sentences, thus the language of scientific writing should not be complex, as Day (1979, p. 5) Medical texts are one of the scientific text types which are written either by and for physicians or for the public.…”
Section: Scientific Genre: Medical Writingmentioning
confidence: 99%